New insight into the molecular basis of hemophilia A - El Maarri, Osman (2006)
Since publication of the sequence of the factor VIII gene (F8) in 1984, a large number of mutations that cause hemophilia A (HA) have been identified.With the technical advances associated with mutation screenings, it is now possible to identify a putative F8 sequence alteration in the great majority of HA patients. The mutation spectrum includes 2 inversion hot spots (intron 1 and intron 22 inversions) mediated by intrachromosomal recombination between 2 copies of long inverted repeats, one of which lies within the F8 gene whereas the other is extragenic. Point mutations are distributed over all of the exons, and deletions or insertions of different sizes and mutations affecting splice sites account for the rest of the known mutations. In a small number of cases, however, we are unable to find any disease-determining DNA changes in the coding regions of the F8 gene. This fact points to possibilities of unknown gene rearrangements that disrupt the F8 gene or mutations in other genes that play a role in the processing/secretion of the factor VIII protein. Moreover, the proof of an absence of F8 messenger RNA (mRNA) in one patient points to either a defect in the expression of F8 mRNA or its rapid degradation, which may represent a novel mechanism leading to HA.